Meningkatkan Kualitas Aplikasi Dengan Menggunakan Metode Design Science Research (DSR) Berdasarkan Analisis TRI dan TAM - Putra, Endi; Suseno, Jenar; Napitupulu, Darmawan (Jurnal Pekommas, 2023)
Abstract – This research is conducted to develop prototype with Design Science Research (DSR) methodology for Fundraising Information System (SANDRA) 2.0 Dompet Dhuafa. SANDRA is a web application which is used to manage donation funds and used by internal employees. However, on the actual condition there are several users complaining about complex data search, long loading time, and complex donation flow. The research is started with first iteration which is accomplished by questionnaire based on combined Technology Readiness Index (TRI) and Technology Acceptance Model (TAM) to determine the factors that affect users’ intention by its users. The result of this is that the users prioritize the usefulness of the application. The development on this research is focused on the minimizing the data searching process and adding new feature to reduce donation process. On the second iteration, the prototype is evaluated by the user’s using questionnaire and interview session with the representative of users. Users feel that the improvement is increasing their performance. By utilizing the DSR methodology, application development can be completed with close fulfilment of the requirement. The result of this research hopefully can be a suggestion for improvement on SANDRA application users and can contribute to academics’ knowledge.